The use of symbols for autistic children in the classroom - Syahriani, Irma; Supriadi (Proceder: Applied Linguistics, Literature, and Language Education, 2023)
Autism spectrum disorder (ASD) is a developmental disability caused by differences in the brain. The characteristic of autistic students is difficulty socializing with other people, lack of interest, limited activity, and frequent repetitive movements. Therefore, the importance of education for autistic children must begin since parents already know their childâ€™s condition. The objectives of this research are to: (1) identify the types of symbols used in teaching autism; and (2) examine the teacher’s use of symbols to interact with autistic students. This research used the qualitative research method. This method is considered â€œreflectiveâ€ which places the researcher in their role as a subject who also utilized observational techniques (direct observations and interviews). The sample employed in this study is purposeful and is based on how well the interviewees answered the questions. The findings of this research demonstrated the value of autism symbols. How one responds to inquiries and other actions might be perceived as developing. The types of symbols are modified to meet the communication needs of people with autism, such as PACS (Picture Archiving and Communication System), COMPIC (Computerized Pictograph), and pictures that are useful teaching tools for use in the classroom. The degree of cooperation and eye contact of autistic students must first come into the teacher’s focus to determine the effectiveness of symbols in teaching. The use of symbols in teaching communication to children with autism is very effective. It is said to be very effective because autistic children can slowly communicate with the people around them even though it takes a very long time.